CD3D and PRKCQ work together to discriminate between B-cell and T-cell acute lymphoblastic leukemia. (1st October 2016) - Ma, Dongli; Zhong, Shan; Liu, Xiaorong; Mai, Huirong; Mai, Guoqin; Xu, Cheng; Zhou, Fengfeng
Abstract: Different therapeutic methods have been developed for the B-cell and T-cell subtypes of acute lymphoblastic leukemia (ALL). The identification of molecular biomarkers that can accurately discriminate between B-cell and T-cell ALLs will facilitate the quick determination of therapeutic plans, as well as reveal the intrinsic mechanisms underlining the two different ALL subtypes. This study computationally screened the high-throughput transcriptome dataset for multiple candidate biomarkers and verified their discrimination abilities in an independent sample set using quantitative real-time polymerase chain reaction (PCR) technology. Both technologies suggest that the two genes CD3D and PKRCQ together provided a good model for classification of B-cell and T-cell ALLs, whereas the individual genes did not show consistent discrimination between the two ALL subtypes. Supplementary material is available athttp://healthinformaticslab.org/supp/ . Highlights: Two-gene biomarker to discriminate B-cell and T-cell acute lymphoblastic leukemia. Integration of both computational and experimental technologies. Transmembrane antigen CD3D and kinase PRKCQ may serve as stable treatment targets.